A method for preparing a high-efficiency composite defoamer

By using components such as sea buckthorn fruit oil, polydimethylsiloxane, modified nanomontmorillonite and silk protein, the challenges of existing defoamers in environmental protection and scope of application are solved, and efficient defoaming, strong stability and environmental protection are achieved.

CN119425165BActive Publication Date: 2025-04-11ZIBO KAIMEIKE IND & TRADE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510025518.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-11
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

Existing silicone defoamers have challenges in environmental protection and scope of application, including environmental pollution, limitations in formulation design and reduced stability.

Method used

High-efficiency composite defoaming agent is prepared by components such as sea buckthorn fruit oil, polydimethylsiloxane, modified nanomontmorillonite and silk protein. The stability and defoaming efficiency of the defoaming agent are improved through emulsification and cross-linking treatment.

Benefits of technology

It achieves the purpose of efficient defoaming, strong stability and environmental protection, improves the biocompatibility and environmental friendliness of the defoaming agent, extends the service life, and maintains efficient performance under complex working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a preparation method of an efficient composite defoamer, belongs to the technical field of defoamers, and comprises the following steps: step S1, mixing seabuckthorn fruit oil with polydimethylsiloxane, adding an emulsifier, high shear stirring, obtaining a mixed solution, and then slowly adding the mixed solution to a thickener solution, stirring evenly, obtaining an emulsion; step S2, dispersing silane-modified nano-montmorillonite in deionized water, adding a degumming treated silk protein solution, then adding a glutaraldehyde solution, stirring at room temperature, filtering, washing, and drying to obtain a modified nano-montmorillonite composite material; step S3, adding the modified nano-montmorillonite composite material to the emulsion, mixing, heating and stirring, and obtaining an efficient composite defoamer. The invention realizes the purpose of efficient defoaming, strong stability and green environmental protection of the defoamer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of defoamers, and in particular to a method for preparing a high-efficiency composite defoamer. Background Art

[0002] Silicone defoamers are a common type of defoamers, widely used in many fields such as industry, chemistry, pharmaceuticals, food, coatings, etc. Silicone defoamers are usually composed of siloxane groups and organic groups. These molecular structures give silicone defoamers unique physical and chemical properties, such as surface activity, low surface tension, high temperature resistance, chemical corrosion resistance, etc. They can effectively reduce surface tension in foam, destroy the foam film structure, and quickly eliminate foam.

[0003] Although silicone defoamers have shown good performance in practical applications, their use and promotion still face some significant challenges. First, from the perspective of environmental protection, silicone defoamers usually accumulate in water bodies for a long time, which may have a negative impact on the ecosystem, especially if they are not properly treated, which may cause environmental pollution problems. Secondly, due to the different needs for defoamers in different industrial scenarios, the formulation design of some silicone defoamers has limitations and cannot achieve the purpose of efficient defoaming.

[0004] Under complex working conditions, such as high temperature and high shear force, some silicone defoamers may also experience reduced stability, resulting in reduced defoaming efficiency, which further limits the scope of application of the defoamer.

[0005] Therefore, it is necessary to provide a method for preparing a high-efficiency composite defoamer to solve the problems existing in the above-mentioned prior art. Summary of the invention

[0006] In view of this, the present invention provides a method for preparing a high-efficiency composite defoaming agent, which can achieve the purpose of high-efficiency defoaming, strong stability and green environmental protection.

[0007] The specific scheme of the present invention is as follows: a method for preparing a high-efficiency composite defoamer.

[0008] Preferably, the method comprises the following steps:

[0009] Step S1, mixing seabuckthorn fruit oil and polydimethylsiloxane, adding an emulsifier, and stirring at high shear to obtain a mixed solution, and then slowly adding the mixed solution to a thickener solution, stirring evenly, to obtain an emulsion;

[0010] Step S2, dispersing the nano-montmorillonite modified with silane in deionized water, adding the degummed silk protein solution, and then adding the glutaraldehyde solution, stirring at room temperature, filtering, washing, and drying to obtain a modified nano-montmorillonite composite material;

[0011] Step S3, adding the modified nano-montmorillonite composite material to the emulsion, mixing, heating and stirring, to obtain a high-efficiency composite defoaming agent.

[0012] Seabuckthorn fruit oil is rich in unsaturated fatty acids, carotenoids, vitamin C and natural surfactants. It has strong lubricity and can quickly penetrate into the foam film, reduce the surface tension of the foam film, and promote the rupture of the foam film. In addition, the surfactants in seabuckthorn fruit oil can improve the wettability, dispersibility and adhesion of the defoamer, promote the uniform distribution of the defoamer in the medium, and improve the defoaming efficiency of the defoamer. The vitamin C and β-carotene contained in seabuckthorn fruit oil are also natural antioxidant ingredients that can effectively resist oxidation reactions, reduce the phenomenon of performance degradation caused by oxidation, and help maintain the long-term stability of the defoamer and help extend the service life of the defoamer. As a natural ingredient, seabuckthorn fruit oil can not only improve the biocompatibility of the defoamer, but also has great advantages in environmental friendliness and sustainability.

[0013] Polydimethylsiloxane has extremely low surface tension and can effectively penetrate into the foam film and quickly reduce the stability of the foam. Especially in high shear and high temperature environments, the defoaming performance is particularly outstanding. Its lubricity and temperature resistance can also enhance the stability of the defoamer. The physical and chemical properties of sea buckthorn oil and polydimethylsiloxane are different. Sea buckthorn oil is a lipophilic component, while polydimethylsiloxane is a silicon-based compound with strong hydrophilicity and lipophilicity, but the miscibility of the two is poor, and stratification or unevenness may occur. Therefore, using an emulsifier to improve the compatibility of the two and promote the formation of a stable emulsion composite system between the two is conducive to improving the stability of the defoamer under different chemical environmental conditions.

[0014] The layered structure and high specific surface area of ​​nano-montmorillonite make it highly adsorbable, and it can be adsorbed on the surface of the foam film or inside the bubbles, affecting the stability of the foam film. After silane modification, nano-montmorillonite can more effectively contact the bubbles in the liquid, promote foam rupture by enhancing lubricity and changing the structure of the foam film, thereby improving the defoaming effect and inhibiting the formation of foam. Silane-modified nano-montmorillonite can also enhance the rheological properties of the defoamer, making the defoamer show better durability and stability during the application process.

[0015] Untreated silk is insoluble in water. After degumming, the internal β-folding structure of silk protein is mostly destroyed, and its structure is transformed into an amorphous state, the water solubility is improved, and a silk protein solution can be prepared to promote subsequent crosslinking and modification. The modified nano-montmorillonite composite material is prepared by using the silk protein solution and silane-modified nano-montmorillonite. By adding glutaraldehyde as a crosslinking agent, the silk protein can form a crosslinking structure on the surface of the silane-modified montmorillonite, which is helpful to improve the toughness and tolerance of the composite material, further enhance the stability of the composite material in a dynamic environment, and the crosslinking structure has a certain thermal stability and hydrolysis resistance, which can slow down the expansion and hydrolysis phenomenon of the nano-montmorillonite, is beneficial to the integrity of the composite material, and also enables the defoamer to maintain an efficient defoaming effect in a high humidity environment. Silk protein has both hydrophobicity and hydrophilicity. This characteristic can assist the modified nano-montmorillonite to show better dispersion and adsorption performance at the gas-liquid interface or in a complex liquid phase environment, accelerate the rupture of bubbles, and achieve the purpose of efficient defoaming of the defoamer. In addition, silk protein, as a natural ingredient, can reduce dependence on organic chemical additives and promote the realization of green environmental protection goals.

[0016] Preferably, in step S1, the weight ratio of seabuckthorn fruit oil to polydimethylsiloxane is 1:(1-1.2); the speed of high shear stirring is 3500-4500 r / min, and the time is 10-15 min.

[0017] Preferably, in step S1, the emulsifier is one of Span60, Span80 and Tween80; the thickener is one of hydroxyethyl cellulose, guar gum and carbomer; the stirring speed is 600-800r / min, the time is 10-15min, and the temperature is 45-55°C.

[0018] Preferably, in step S1, an antioxidant is added before obtaining the emulsion and stirred at a speed of 500-600 r / min for 5-10 min; the antioxidant is one of BHT and vitamin E.

[0019] Preferably, in step S2, the silk protein solution is obtained by the following degumming process: the silk is placed in a sodium carbonate solution and boiled for degumming, then dissociated with a lithium bromide solution, and finally dialyzed with deionized water to obtain the silk protein solution; the concentration of the silk protein solution is 2-3wt%; the concentration of the glutaraldehyde solution is 0.1-0.2wt%; the stirring speed at room temperature is 200-300r / min, and the time is 2-4h.

[0020] The silk is degummed by boiling, and the degummed silk protein is then added to a lithium bromide solution to dissociate the crystal structure so that the silk protein can be dissolved in water to form a solution. Finally, deionized water is used for dialyzation to remove impurities and improve the purity of the silk protein solution.

[0021] Preferably, in step S3, the preparation of silane-modified nano-montmorillonite comprises the following steps: adding nano-montmorillonite to a silane modifier solution, heating and stirring, filtering, and drying to obtain silane-modified nano-montmorillonite.

[0022] Natural nano-montmorillonite particles are usually highly hydrophilic, with poor dispersibility in oil-water or oil-based systems, and are prone to agglomeration or sedimentation. Through silanization treatment, hydrophobic groups can be introduced on its surface to improve its dispersibility in oil-based systems. In addition, the modified nano-montmorillonite can maintain stability in complex environments due to its stable structure and chemical bonding, which helps the defoamer to maintain efficient defoaming performance under high temperature, high pH and other conditions. In addition, silane modification usually uses low-toxic, environmentally friendly silane modifiers, which makes the defoamer containing silane-modified nano-montmorillonite have better application prospects and meet the requirements of green chemistry.

[0023] Preferably, the silane modifier is one of tetraethyl orthosilicate, methyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane; the heating and stirring speed is 600-800 r / min, the temperature is 60-70° C., and the time is 80-90 min.

[0024] Preferably, in step S3, the heating and stirring speed is 1000-1200 r / min, the time is 30-40 min, and the temperature is 40-50°C.

[0025] Preferably, the defoamer comprises the following components in parts by weight:

[0026] 5-12 parts of polydimethylsiloxane, 1-3 parts of emulsifier, 3-5 parts of modified nano-montmorillonite composite material, 70-80 parts of thickener solution and 5-10 parts of sea buckthorn fruit oil.

[0027] Preferably, the defoamer further comprises the following components in parts by weight:

[0028] Antioxidant 0.1-0.2 parts;

[0029] The modified nano-montmorillonite composite material comprises the following raw materials in parts by weight: 5-8 parts of nano-montmorillonite, 90-95 parts of silane modifier solution, 60-70 parts of deionized water, 25-35 parts of degummed silk protein solution and 15-20 parts of glutaraldehyde solution.

[0030] The above technical solution of the present invention includes at least the following beneficial effects:

[0031] (1) Sea buckthorn fruit oil is rich in unsaturated fatty acids and natural surfactants, which can quickly penetrate into the foam film, reduce its surface tension, promote foam bursting, and improve the wettability, dispersibility and adhesion of the defoaming agent, which helps to evenly distribute the defoaming agent in the medium, improve the defoaming efficiency of the defoaming agent, and achieve the purpose of efficient defoaming.

[0032] (2) Seabuckthorn fruit oil is rich in natural antioxidant ingredients such as vitamin C and β-carotene, which can reduce stability problems caused by oxidation and help improve the long-term stability of defoamers. As a natural ingredient, seabuckthorn fruit oil can not only improve the biocompatibility of defoamers, but also has great advantages in terms of environmental friendliness and sustainability.

[0033] (3) Nano-montmorillonite has strong adsorption and can be adsorbed on the surface of the foam film or inside the bubbles, affecting the stability of the foam film and promoting the rupture of the foam. Silane modification improves the dispersibility of nano-montmorillonite, further promotes the improvement of defoaming efficiency, and can also inhibit the generation of foam.

[0034] (4) The modified nano-montmorillonite composite material prepared by the present invention can form a cross-linked structure on the surface of the silane-modified nano-montmorillonite, which can slow down the swelling and hydrolysis of the nano-montmorillonite, and is conducive to the defoaming agent to maintain a high efficiency defoaming effect in a high humidity environment. The amphiphilic nature of silk protein can assist the modified nano-montmorillonite to show better dispersion and adsorption performance in a complex liquid phase environment, accelerate the rupture of bubbles, and achieve the purpose of high efficiency defoaming of the defoaming agent. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0036] Example 1

[0037] 8 parts of seabuckthorn fruit oil and 8 parts of polydimethylsiloxane were uniformly mixed, 1.5 parts of emulsifier Span60 were added, and a high shear mixer was used to continuously stir at a speed of 4500r / min for 10 minutes to ensure that the components were fully mixed to obtain a mixed solution, and the prepared mixed solution was slowly added to 75 parts of 0.2wt% hydroxyethyl cellulose solution. During this process, the temperature of the system was increased to 50°C, and while adding the mixed solution, it was stirred at a speed of 700r / min for 12 minutes to ensure that the thickener and the mixed solution were fully mixed and evenly dispersed. After the system was uniform, 0.15 parts of antioxidant BHT were added, and then stirring was continued at a speed of 550r / min for 8 minutes until the mixed solution was completely uniform to obtain an emulsion.

[0038] 6 parts of nano-montmorillonite were mixed with 93 parts of 1.0wt% methyltriethoxysilane solution, heated to 65°C, stirred, and stirred at a speed of 700r / min for 85min to allow the silane modifier to fully react with the nano-montmorillonite. After stirring, the mixture was filtered and washed to remove the residual silane modifier. Finally, the washed solid was dried to obtain silane-modified nano-montmorillonite.

[0039] 2 parts of silk were put into 0.3wt% sodium carbonate solution and boiled for degumming, then dissociated with 80wt% lithium bromide solution, and finally dialyzed with deionized water to obtain a silk protein solution, and prepared into a 2wt% silk protein solution. Silane-modified nano-montmorillonite was dispersed in 65 parts of deionized water, 30 parts of the 2wt% silk protein solution after the above degumming treatment and 15 parts of 0.15wt% glutaraldehyde solution were added, stirred at room temperature at a speed of 300r / min for 4h, filtered, washed, and dried to obtain a modified nano-montmorillonite composite material.

[0040] Add 4 parts of modified nano-montmorillonite composite material to the above emulsion, heat to 45°C, start stirring, the stirring speed is 1100r / min, the time is 35min, and after ensuring uniform mixing, a high-efficiency composite defoaming agent is obtained.

[0041] Example 2

[0042] 5 parts of seabuckthorn fruit oil and 6 parts of polydimethylsiloxane were uniformly mixed, 1 part of emulsifier Tween80 was added, and a high shear mixer was used to continuously stir at a speed of 4200r / min for 12 minutes to ensure that the components were fully mixed to obtain a mixed solution, and the prepared mixed solution was slowly added to 70 parts of 0.25wt% guar gum solution. During this process, the temperature of the system was increased to 55°C, and while adding the mixed solution, it was stirred at a speed of 750r / min for 10 minutes to ensure that the thickener and the mixed solution were fully mixed and evenly dispersed. After the system was uniform, 0.2 parts of antioxidant vitamin E were added, and then stirred at a speed of 600r / min for 5 minutes until the mixed solution was completely uniform to obtain an emulsion.

[0043] 8 parts of nano-montmorillonite were mixed with 95 parts of 2.0wt% tetraethyl orthosilicate solution, heated to 70°C, and stirred at 600r / min for 90min to allow the silane modifier to fully react with the nano-montmorillonite. After stirring, the mixture was filtered and washed to remove the residual silane modifier. Finally, the washed solid was dried to obtain silane-modified nano-montmorillonite.

[0044] 2 parts of silk were put into 0.3wt% sodium carbonate solution and boiled for degumming, then dissociated with 80wt% lithium bromide solution, and finally dialyzed with deionized water to obtain a silk protein solution, and a 2.5wt% silk protein solution was prepared. Silane-modified nano-montmorillonite was dispersed in 70 parts of deionized water, 25 parts of the 2.5wt% silk protein solution after the above degumming treatment and 18 parts of 0.2wt% glutaraldehyde solution were added, stirred at room temperature at a speed of 200r / min for 4.5h, filtered, washed, and dried to obtain a modified nano-montmorillonite composite material.

[0045] Add 5 parts of modified nano-montmorillonite composite material to the above emulsion, heat to 45°C, start stirring, and stir at a speed of 1050r / min for 35min to ensure uniform mixing to obtain a high-efficiency composite defoaming agent.

[0046] Example 3

[0047] 10 parts of seabuckthorn fruit oil and 11 parts of polydimethylsiloxane were uniformly mixed, 3 parts of emulsifier Span80 were added, and a high shear mixer was used to continuously stir at a speed of 3500r / min for 15 minutes to ensure that the components were fully mixed to obtain a mixed solution, and the prepared mixed solution was slowly added to 80 parts of 0.15wt% hydroxyethyl cellulose solution. During this process, the temperature of the system was increased to 45°C, and while adding the mixed solution, it was stirred at a speed of 600r / min for 15 minutes to ensure that the thickener and the mixed solution were fully mixed and evenly dispersed. After the system was uniform, 0.1 parts of antioxidant vitamin E were added, and stirring was continued at a speed of 600r / min for 7 minutes until the mixed solution was completely uniform to obtain an emulsion.

[0048] 5 parts of nano-montmorillonite were mixed with 90 parts of 1.0wt% γ-glycidyloxypropyltrimethoxysilane solution, heated to 60°C, stirred, and stirred at 750r / min for 80min to allow the silane modifier to fully react with the nano-montmorillonite. After stirring, the mixture was filtered and washed to remove the residual silane modifier. Finally, the washed solid was dried to obtain silane-modified nano-montmorillonite.

[0049] 3 parts of silk were put into 0.5wt% sodium carbonate solution and boiled for degumming, then dissociated with 82wt% lithium bromide solution, and finally dialyzed with deionized water to obtain a silk protein solution, and a 3wt% silk protein solution was prepared. Silane-modified nano-montmorillonite was dispersed in 65 parts of deionized water, 25 parts of the 3wt% silk protein solution after the above degumming treatment and 20 parts of 0.1wt% glutaraldehyde solution were added, and the reaction was stirred at 270r / min at room temperature for 3h, filtered, washed, and dried to obtain a modified nano-montmorillonite composite material.

[0050] Add 4 parts of modified nano-montmorillonite composite material to the above emulsion, heat to 50°C, start stirring, the stirring speed is 1000r / min, the time is 40min, and after ensuring uniform mixing, a high-efficiency composite defoaming agent is obtained.

[0051] Example 4

[0052] 9 parts of seabuckthorn fruit oil and 10 parts of polydimethylsiloxane were uniformly mixed, 2.5 parts of emulsifier Span80 were added, and a high shear mixer was used to continuously stir at a speed of 4000r / min for 12 minutes to ensure that the components were fully mixed to obtain a mixed solution, and the prepared mixed solution was slowly added to 70 parts of 0.3wt% guar gum solution. During this process, the temperature of the system was increased to 52°C, and while adding the mixed solution, it was stirred at a speed of 800r / min for 10 minutes to ensure that the thickener and the mixed solution were fully mixed and uniformly dispersed to obtain an emulsion.

[0053] 6 parts of nano-montmorillonite were mixed with 95 parts of 1.5wt% γ-glycidyloxypropyltrimethoxysilane solution, heated to 70°C, stirred, and stirred at a speed of 800r / min for 85min to allow the silane modifier to fully react with the nano-montmorillonite. After stirring, the mixture was filtered and washed to remove the residual silane modifier. Finally, the washed solid was dried to obtain silane-modified nano-montmorillonite.

[0054] 2 parts of silk were put into 0.4wt% sodium carbonate solution and boiled for degumming, then dissociated with 85wt% lithium bromide solution, and finally dialyzed with deionized water to obtain a silk protein solution, and a 2wt% silk protein solution was prepared. Silane-modified nano-montmorillonite was dispersed in 60 parts of deionized water, 35 parts of the 2wt% silk protein solution after the above degumming treatment and 15 parts of 0.15wt% glutaraldehyde solution were added, stirred at room temperature at a speed of 250r / min for 5h, filtered, washed, and dried to obtain a modified nano-montmorillonite composite material.

[0055] Add 3 parts of modified nano-montmorillonite composite material to the above emulsion, heat to 45°C, start stirring, and stir at a speed of 1200r / min for 30min to ensure uniform mixing to obtain a high-efficiency composite defoaming agent.

[0056] Example 5

[0057] 6 parts of seabuckthorn fruit oil and 6 parts of polydimethylsiloxane were uniformly mixed, 1 part of emulsifier Span60 was added, and a high shear mixer was used to continuously stir at a speed of 4500r / min for 10 minutes to ensure that the components were fully mixed to obtain a mixed solution, and the prepared mixed solution was slowly added to 75 parts of 0.25wt% guar gum solution. During this process, the temperature of the system was increased to 47°C, and while adding the mixed solution, it was stirred at a speed of 800r / min for 10 minutes to ensure that the thickener and the mixed solution were fully mixed and evenly dispersed. After the system was uniform, 0.15 parts of antioxidant vitamin E were added, and then stirred at a speed of 500r / min for 10 minutes until the mixed solution was completely uniform to obtain an emulsion.

[0058] 7 parts of nano-montmorillonite were mixed with 93 parts of 1.0wt% methyltriethoxysilane solution, heated to 65°C, stirred, and stirred at a speed of 650r / min for 90min to allow the silane modifier to fully react with the nano-montmorillonite. After stirring, the mixture was filtered and washed to remove the residual silane modifier. Finally, the washed solid was dried to obtain silane-modified nano-montmorillonite.

[0059] 2 parts of silk were put into 0.4wt% sodium carbonate solution and boiled for degumming, then dissociated with 82wt% lithium bromide solution, and finally dialyzed with deionized water to obtain a silk protein solution, and a 2.5wt% silk protein solution was prepared. Silane-modified nano-montmorillonite was dispersed in 66 parts of deionized water, 32 parts of the 2.5wt% silk protein solution after the above degumming treatment and 17 parts of 0.1wt% glutaraldehyde solution were added, and the reaction was stirred at 300r / min at room temperature for 3h, filtered, washed, and dried to obtain a modified nano-montmorillonite composite material.

[0060] Add 5 parts of modified nano-montmorillonite composite material to the above emulsion, heat to 45°C, start stirring, and stir at a speed of 1150r / min for 40min to ensure uniform mixing to obtain a high-efficiency composite defoaming agent.

[0061] Example 6

[0062] 7 parts of seabuckthorn fruit oil and 8 parts of polydimethylsiloxane were uniformly mixed, 2 parts of emulsifier Tween80 were added, and a high shear mixer was used to continuously stir at a speed of 3800r / min for 13 minutes to ensure that the components were fully mixed to obtain a mixed solution, and the prepared mixed solution was slowly added to 80 parts of 0.1wt% carbomer solution. During this process, the temperature of the system was increased to 45°C, and while adding the mixed solution, it was stirred at a speed of 700r / min for 15 minutes to ensure that the thickener and the mixed solution were fully mixed and evenly dispersed. After the system was uniform, 0.2 parts of antioxidant BHT were added, and then stirring was continued at a speed of 520r / min for 8 minutes until the mixed solution was completely uniform to obtain an emulsion.

[0063] 5 parts of nano-montmorillonite were mixed with 90 parts of 0.5wt% tetraethyl orthosilicate solution, heated to 65°C, stirred, and stirred at 700r / min for 80min to allow the silane modifier to fully react with the nano-montmorillonite. After stirring, the mixture was filtered and washed to remove the residual silane modifier. Finally, the washed solid was dried to obtain silane-modified nano-montmorillonite.

[0064] 2 parts of silk were put into 0.5wt% sodium carbonate solution and boiled for degumming, then dissociated with 80wt% lithium bromide solution, and finally dialyzed with deionized water to obtain a silk protein solution, and a 3wt% silk protein solution was prepared. Silane-modified nano-montmorillonite was dispersed in 63 parts of deionized water, 30 parts of the 3wt% silk protein solution after the above degumming treatment and 18 parts of 0.2wt% glutaraldehyde solution were added, and the reaction was stirred at 250r / min at room temperature for 4h, filtered, washed, and dried to obtain a modified nano-montmorillonite composite material.

[0065] Add 5 parts of modified nano-montmorillonite composite material to the above emulsion, heat to 50°C, start stirring, and stir at a speed of 1200r / min for 35min to ensure uniform mixing to obtain a high-efficiency composite defoaming agent.

[0066] Example 7

[0067] 10 parts of seabuckthorn fruit oil and 12 parts of polydimethylsiloxane were uniformly mixed, 3 parts of emulsifier Span80 were added, and a high shear mixer was used to continuously stir at a speed of 3500r / min for 15 minutes to ensure that the components were fully mixed to obtain a mixed solution, and the prepared mixed solution was slowly added to 73 parts of 0.25wt% guar gum solution. During this process, the temperature of the system was increased to 55°C, and while adding the mixed solution, it was stirred at a speed of 650r / min for 12 minutes to ensure that the thickener and the mixed solution were fully mixed and evenly dispersed. After the system was uniform, 0.1 parts of antioxidant BHT were added, and then stirring was continued at a speed of 600r / min for 7 minutes until the mixed solution was completely uniform to obtain an emulsion.

[0068] 8 parts of nano-montmorillonite were mixed with 95 parts of 1.8 wt% γ-glycidyloxypropyltrimethoxysilane solution, heated to 70°C, stirred, and stirred at 750 r / min for 85 min to allow the silane modifier to fully react with the nano-montmorillonite. After stirring, the mixture was filtered and washed to remove the residual silane modifier. Finally, the washed solid was dried to obtain silane-modified nano-montmorillonite.

[0069] 3 parts of silk were put into 0.3wt% sodium carbonate solution and boiled for degumming, then dissociated with 85wt% lithium bromide solution, and finally dialyzed with deionized water to obtain a silk protein solution, and prepared into a 2wt% silk protein solution. Silane-modified nano-montmorillonite was dispersed in 70 parts of deionized water, 25 parts of the 2wt% silk protein solution after the above degumming treatment and 15 parts of 0.15wt% glutaraldehyde solution were added, stirred at room temperature at a speed of 200r / min for 5h, filtered, washed, and dried to obtain a modified nano-montmorillonite composite material.

[0070] Add 4 parts of modified nano-montmorillonite composite material to the above emulsion, heat to 40°C, start stirring, and stir at a speed of 1000r / min for 40min to ensure uniform mixing to obtain a high-efficiency composite defoaming agent.

[0071] Example 8

[0072] 5 parts of seabuckthorn fruit oil and 5 parts of polydimethylsiloxane were uniformly mixed, 1 part of emulsifier Tween80 was added, and a high shear mixer was used to continuously stir at a speed of 4200r / min for 12 minutes to ensure that the components were fully mixed to obtain a mixed solution, and the prepared mixed solution was slowly added to 70 parts of 0.1wt% carbomer solution. During this process, the temperature of the system was increased to 52°C, and while adding the mixed solution, it was stirred at a speed of 750r / min for 12 minutes to ensure that the thickener and the mixed solution were fully mixed and uniformly dispersed to obtain an emulsion.

[0073] 7 parts of nano-montmorillonite were mixed with 92 parts of 2.0wt% methyltriethoxysilane solution, heated to 60°C, stirred, and stirred at a speed of 600r / min for 85min to allow the silane modifier to fully react with the nano-montmorillonite. After stirring, the mixture was filtered and washed to remove the residual silane modifier. Finally, the washed solid was dried to obtain silane-modified nano-montmorillonite.

[0074] 2 parts of silk were put into 0.3wt% sodium carbonate solution and boiled for degumming, then dissociated with 80wt% lithium bromide solution, and finally dialyzed with deionized water to obtain a silk protein solution, and a 2wt% silk protein solution was prepared. Silane-modified nano-montmorillonite was dispersed in 60 parts of deionized water, 30 parts of the 2.5wt% silk protein solution after the above degumming treatment and 20 parts of 0.1wt% glutaraldehyde solution were added, and the reaction was stirred at a speed of 280r / min at room temperature for 3.5h, filtered, washed, and dried to obtain a modified nano-montmorillonite composite material.

[0075] Add 3 parts of modified nano-montmorillonite composite material to the above emulsion, heat to 50°C, start stirring, and stir at a speed of 1100r / min for 35min to ensure uniform mixing to obtain a high-efficiency composite defoaming agent.

[0076] The present invention also carries out comparative examples and related tests.

[0077] Comparative Example 1

[0078] The difference between Comparative Example 1 and Example 3 is that sea buckthorn fruit oil is not used, and other compositions and preparation methods are the same as those of Example 3, and a high-efficiency composite defoaming agent is prepared.

[0079] Comparative Example 2

[0080] The difference between Comparative Example 2 and Example 3 is that no modified nano-montmorillonite composite material is prepared, but only silane-modified nano-montmorillonite is used, and the other compositions and preparation methods are the same as those of Example 3, and a high-efficiency composite defoaming agent is prepared.

[0081] Comparative Example 3

[0082] The difference between Comparative Example 3 and Example 3 is that only silk protein solution and nano-montmorillonite are used in the modified nano-montmorillonite composite material, and other compositions and preparation methods are the same as those of Example 3, and a high-efficiency composite defoaming agent is prepared.

[0083] Performance testing

[0084] The defoaming effect of the defoaming agents prepared in Examples 1-8 and Comparative Examples 1-3 was tested according to the following reference standards.

[0085] Referring to GB / T 26527-2011 silicone defoamer standard, the defoaming performance test was carried out at room temperature and 60°C respectively. 50mL of standard foaming solution was measured with a stoppered measuring cylinder, 0.2g of defoamer was added, the bottle stopper was covered, and the measuring cylinder was vertically shaken up and down 100 times at a frequency of 2 times / s and a swing amplitude of 30-35cm. The measuring cylinder was left to stand and timed, and the time taken for the foam to disappear until the liquid surface appeared was recorded in seconds; the antifoaming performance was measured with a circulating bubbler. The test results are shown in Table 1 below.

[0086] Table 1

[0087]

[0088] From the data in Table 1, it can be seen that the defoaming performance and foam suppression performance of the defoamer prepared in Comparative Example 1 are much lower than those of the defoamer prepared in Example 3 at room temperature and 60°C, indicating that the use of seabuckthorn fruit oil increases the surfactant in the defoamer and significantly improves the rapid defoaming ability of the defoamer; at room temperature and 60°C, the defoaming performance and foam suppression performance of the defoamer prepared in Comparative Example 2 are also significantly reduced compared with Example 3, indicating that silk protein can significantly enhance the defoaming effect of silane-modified nano-montmorillonite, thereby improving the defoaming efficiency of the defoamer; the defoamer prepared in Comparative Example 3 has lower performance at room temperature and 60°C than the defoamers prepared in Examples 1-8, indicating that the composite material prepared using only silk protein and nano-montmorillonite cannot achieve the purpose of efficient defoaming of the defoamer, nor can it achieve rapid defoaming at a higher temperature.

[0089] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a high-efficiency composite defoamer, characterized in that: The following steps are involved: Step S1, mixing seabuckthorn fruit oil and polydimethylsiloxane, adding an emulsifier, and stirring at high shear to obtain a mixed solution, and then slowly adding the mixed solution to a thickener solution, stirring evenly, to obtain an emulsion; Step S2, dispersing the nano-montmorillonite modified with silane in deionized water, adding the degummed silk protein solution, and then adding the glutaraldehyde solution, stirring at room temperature, filtering, washing, and drying to obtain a modified nano-montmorillonite composite material; Step S3, adding the modified nano-montmorillonite composite material to the emulsion, mixing, heating and stirring, to obtain a high-efficiency composite defoaming agent.

2. The method for preparing a high-efficiency composite defoamer according to claim 1, characterized in that: In the step S1, the weight ratio of seabuckthorn fruit oil to polydimethylsiloxane is 1:(1-1.2); the speed of high shear stirring is 3500-4500 r / min, and the time is 10-15 min.

3. The method for preparing a high-efficiency composite defoamer according to claim 1, characterized in that: In step S1, the emulsifier is one of Span60, Span80 and Tween80; the thickener solution is one of hydroxyethyl cellulose solution, guar gum solution and carbomer solution; the concentration of the thickener solution is 0.1-0.3wt%; the stirring speed is 600-800r / min, the time is 10-15min, and the temperature is 45-55°C.

4. The method for preparing a high-efficiency composite defoamer according to claim 1, characterized in that: In the step S1, an antioxidant is added before obtaining the emulsion and stirred at a speed of 500-600 r / min for 5-10 min; the antioxidant is one of BHT and vitamin E.

5. The method for preparing a high-efficiency composite defoamer according to claim 1, characterized in that: In the step S2, the silk protein solution is obtained by the following degumming process: the silk is put into a sodium carbonate solution and boiled for degumming, then the silk is dissociated with a lithium bromide solution, and finally the silk protein solution is obtained by dialyzing with deionized water; The concentration of the silk protein solution is 2-3wt%; the concentration of the glutaraldehyde solution is 0.1-0.2wt%; the stirring speed at room temperature is 200-300r / min, and the time is 2-4h.

6. The method for preparing a high-efficiency composite defoamer according to claim 1, characterized in that: In the step S2, the preparation of silane-modified nano-montmorillonite includes the following steps: adding nano-montmorillonite into a silane modifier solution, stirring, filtering, and drying to obtain silane-modified nano-montmorillonite.

7. The method for preparing a high-efficiency composite defoamer according to claim 6, characterized in that: The silane modifier solution comprises one of tetraethyl orthosilicate solution, methyltriethoxysilane solution and γ-glycidyloxypropyltrimethoxysilane solution; the concentration of the silane modifier solution is 0.5-2.0wt%; the stirring speed is 600-800r / min, the temperature is 60-70°C, and the time is 80-90min.

8. The method for preparing a high-efficiency composite defoamer according to claim 1, characterized in that: In step S3, the heating and stirring speed is 1000-1200 r / min, the time is 30-40 min, and the temperature is 40-50°C.

9. The method for preparing a high-efficiency composite defoamer according to claim 1, characterized in that: The defoamer comprises the following components in parts by weight: 5-12 parts of polydimethylsiloxane, 1-3 parts of emulsifier, 3-5 parts of modified nano-montmorillonite composite material, 70-80 parts of thickener solution and 5-10 parts of sea buckthorn fruit oil.

10. The method for preparing a high-efficiency composite defoamer according to claim 9, characterized in that: The defoamer also includes the following components in parts by weight: Antioxidant 0.1-0.2 parts; The modified nano-montmorillonite composite material comprises the following raw materials in parts by weight: 5-8 parts of nano-montmorillonite, 90-95 parts of silane modifier solution, 60-70 parts of deionized water, 25-35 parts of degummed silk protein solution and 15-20 parts of glutaraldehyde solution.

Citation Information

Patent Citations

  • Dogwood kernel modified active carbon water purifier and preparation method thereof

    CN103566872A

  • Mineral oil defoamer and preparation method thereof

    CN110960891A